2010
DOI: 10.1080/01924788.2010.501485
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Bedtime Massage on Relaxation in Nursing Home Residents with Sleep Disorders

Abstract: This study evaluated the effectiveness of an activity-based intervention (massage) in producing a relaxation response and sleep in nursing home residents. Using a 2 (intervention, control) × 3 (baseline, intervention, withdrawal) mixed design with random assignment to the intervention (n = 15) or control (n = 13) group, results indicated that the massage produced a statistically significant relaxation response as measured by heart rate (p < .001), systolic and diastolic blood pressure (p = .01), and anxiety (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
4
0
2
Order By: Relevance
“…above the solar plexus Positive; Visser’s Sleep Quality Assessment; Improved sleep quality Chen, 1999 [ 21 ] RCT Nursing home ( n = 1), N = 84, mean age 79, 61.9% men Touch: 15 min of acupressure, consisting of 5 min of finger massage and 10 min of acupoint massage between 1 pm and 10 pm 5 days per week for 3 weeks Positive; Pittsburgh Sleep Quality Index; Significantly more positive sleep including quality, latency, duration, efficiency; reduced disturbances of sleep; and frequencies of nocturnal awakening and night wakeful time. Harris, 2012 [ 69 ] RCT Nursing home ( n = 4), N = 40, mean age 86, 22.5% men, with dementia Touch: 3-min slow-stroke back massage at bedtime for 2 nights None; Actigraphy; No significant increase in minutes of nighttime sleep Nelson, 2010 [ 74 ] RCT Nursing home ( n = 4), N = 28, mean age 69.5, 57.1% men Touch: 15-min massage to head, neck shoulders, and back between 8 pm and 10 pm every night and 7 days None; Observed 3 participants asleep following the intervention Reza, 2010 [ 59 ] RCT (3 groups: intervention, sham, and control) Nursing home ( n = 1), N = 77, mean age 75.2, 53.2% men Touch: 3 sessions of acupressure (hands, head, ears, and feet) per week for 4 weeks Positive; Pittsburgh Sleep Quality Index; Compared to controls, the acupressure group had significantly positive subjective sleep quality, sleep latency, sleep duration, habitual sleep efficiency, sleep sufficiency, and reduced sleep disturbance. No differences between the sham and control groups.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…above the solar plexus Positive; Visser’s Sleep Quality Assessment; Improved sleep quality Chen, 1999 [ 21 ] RCT Nursing home ( n = 1), N = 84, mean age 79, 61.9% men Touch: 15 min of acupressure, consisting of 5 min of finger massage and 10 min of acupoint massage between 1 pm and 10 pm 5 days per week for 3 weeks Positive; Pittsburgh Sleep Quality Index; Significantly more positive sleep including quality, latency, duration, efficiency; reduced disturbances of sleep; and frequencies of nocturnal awakening and night wakeful time. Harris, 2012 [ 69 ] RCT Nursing home ( n = 4), N = 40, mean age 86, 22.5% men, with dementia Touch: 3-min slow-stroke back massage at bedtime for 2 nights None; Actigraphy; No significant increase in minutes of nighttime sleep Nelson, 2010 [ 74 ] RCT Nursing home ( n = 4), N = 28, mean age 69.5, 57.1% men Touch: 15-min massage to head, neck shoulders, and back between 8 pm and 10 pm every night and 7 days None; Observed 3 participants asleep following the intervention Reza, 2010 [ 59 ] RCT (3 groups: intervention, sham, and control) Nursing home ( n = 1), N = 77, mean age 75.2, 53.2% men Touch: 3 sessions of acupressure (hands, head, ears, and feet) per week for 4 weeks Positive; Pittsburgh Sleep Quality Index; Compared to controls, the acupressure group had significantly positive subjective sleep quality, sleep latency, sleep duration, habitual sleep efficiency, sleep sufficiency, and reduced sleep disturbance. No differences between the sham and control groups.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies indicated positive findings ( n = 24) of non-pharmacological interventions in improving nighttime sleep outcomes [ 21 28 , 30 , 32 , 34 , 39 , 42 , 44 , 48 50 , 57 – 63 ] whereas 11 studies reported mixed findings (both positive and none) [ 29 , 31 , 36 , 43 , 45 47 , 51 , 53 , 64 , 65 ]. Although reporting other positive outcomes, 19 studies found no change in nighttime sleep quality after the intervention [ 33 , 35 , 37 , 38 , 40 , 41 , 52 , 54 56 , 66 74 ]. The results differed among location sites, with studies conducted in assisted-living facilities reporting a higher proportion of positive findings than those in nursing homes (70 and 35.7%, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(19,23) Bazı non-farmakolojik yöntemler hemşireler tarafından uygulanabilmektedir. Bunlar, bilişsel-davranışsal terapi (uyaran kontrolü, uyku kısıtlaması, gevşeme tedavisi), (19,20,23) çevresel düzenleme (parlak ışık tedavisi), bakım vericilerin rolü (gece idrar kaçırma yönetimi), (21,22,24,25) uyaran girişimleri (aromaterapi, yatak masajı, müzik) (22,26,27) ve fiziksel ve sosyal girişimler (parmak akupunkturu, Tai Chi programı vb.) (27)(28)(29)(30) şeklinde guruplandırılabilir.…”
unclassified
“…(15) In some of the cases, the intervention induced sleep, decreased sleep disruptions, and improved the overall sleep quality.…”
mentioning
confidence: 99%